The Art of Interacting with Nature: Results of the Experimental Module "Harmony and Environment through Participatory Techniques and Art Therapy" - Teresa Fernández de Juan; Laurie Silvan Nogaim (Arteterapia)
This article summarizes the “Environment and inner harmony” module carried out during the “Social Integration and Self-esteem” project developed in Northern Baja California with a pilot sample of 100 people, including children, young people and adults. Based on previous international research experiences and the practical results of local environmental organizations, the approaches were selected with the objective of achieving an effective connection to the environment. The methodology can be replicated in similar groups.